PROSES PENYEMBUHAN LUKA OPERASI FASE INFLAMASI DENGAN TINDAKAN MOBILISASI DINI PASIEN POST SECTIO CAESAREA DI RSAD WIRA BHAKTI MATARAM - Nurul Auliya Kamila; Rosa Mutianingsih (Jurnal Penelitian, 2022)
Early mobilization is a supporting factor in accelerating postoperative wound recovery and can prevent postoperative complications. By early mobilization, vascularization will be better so that it will affect post sectio caesarea wound healing because the wound requires good blood circulation for cell growth or repair. Based on the results of preliminary study interviews conducted by 9 out of 10 postpartum mothers after sectio caesarea, they were afraid to do early mobilization. One of the reasons was that postpartum mothers were afraid that the surgical sutures would come off. This study aims to determine the effectiveness of early mobilization with the wound healing process of sectio caesarea at the Wira Bhakti Hospital Mataram. The research design used is analytical observational. The sampling technique in this study used an accidental sampling technique with inclusion and exclusion criteria with a sample of 30 respondents and data scollection using an observation sheet.Based on the results of the study, it was found that from 30 respondents postpartum mothers who were examined were more likely to do early mobilization in the first 6-10 hours, namely 23 people (76.7%) and those who experienced wound healing in the inflammatory phase 0-3 days post-sectio. caesarea, namely 23 people (76.7%) and those who did not recover were none. While respondents who did not do early mobilization 10 hours post sectio caesarea were 7 people (23.3%) and those who experienced wound healing in the inflammatory phase 0-3 days post sectio caesarea were none and those who did not heal were 7 people (23, 3%).Based on the results of the chi-square test, the p value is 0.000 with a = 0.05 then (p a), because p 0.05 means Ho is rejected and Ha is accepted so early mobilization of post sectio caesarea patients is effective in the wound healing process in the surgical phase. inflammation 0-3 days at Wira Bhakti Hospital Mataram in 2017. This study can be used as input in the context of implementing midwifery care programs, especially early mobilization for the first 6-10 hours of post sectio caesarea to be improved so that it is hoped that all patients who perform early mobilization in the first 6-10 hours of post sectio caesarea experience surgical wound healing.